ICAAS - Integrated System for lasting Accelerated Aging of MV Cables, Data Monitoring and Acquisition - Mladenovic, Ivana; Weindl, Christian (Electrical Insulation and Dielectric Phenomena, 2009)
A reliable knowledge of the network components condition is of primary importance for creating an optimal investment and maintenance plan for electrical distribution networks. A commonly used tool for this purpose is a partial discharge measurement and analysis. It enables a good overview over the electrical equipment condition and in this way also a prediction of possible service failures. In the case of paper insulated lead cover (PILC) cables, there are still no established criteria for assuming the time to the next failure. Therefore, an accelerated aging system assigned to this cable type was developed, built up and tested. It facilitates a highly sensitive and selective PD-detection and accurate tan(δ)-measurements. Furthermore, by the constant monitoring of the entire aging process, a knowledge data-base is formed up, and the later development of sophisticated diagnostic criteria based on the physical aging process is made possible. In this paper the basic principles and the functionality of a novel system for the accelerated ageing of MV cables called ICAAS (Integrated Cable Accelerated Ageing System) are presented. © 2009 IEEE .
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.icaasi